Students' Creative Thinking in Solving Numeracy Problems Based on Cognitive Style - Alfillaili, Efi; Tristanti, Lia Budi; Nurwiani, Nurwiani (Jurnal VARIDIKA, 2023)
The research aims to describe the character of solving numeracy problems based on students' cognitive styles. Research instruments include teacher questionnaires, cognitive style test instruments, numeracy problem-solving test instruments, interview guides, and documentation. Data from cognitive style tests and interviews are explained descriptively to select research subjects. The subjects of this research were 32 students in class VIII of state junior high schools in Jombang. Data from numeracy tests, interviews, and documentation were analyzed to describe the subject's creative thinking abilities. The results of the research show that field-independent students think of more than one answer in a variety of ways, and succeed in breaking down the details of an idea object into different ways or methods. It also fulfills the creative thinking indicators of novelty and provides a new art in solving numeracy problems that is pure. Meanwhile, field-dependent students have not provided different ideas or ideas as a form of process for solving numeracy problems in different ways. Even though the field-dependent student provided a correct solution to the problem, it did not meet the novelty indicator.